Cytogenetic and molecular profile of endometrial stromal sarcoma - Micci, Francesca (Genes Chromosomes Cancer, 2016)
Recent cytogenetic and molecular investigations have improved our understanding of endometrial stromal tumors, including sarcomas (ESS), and helped redefine their classification into more pathogenetically meaningful categories. Because much more can be gained through such studies, we add information on another 22 ESS examined by karyotyping, PCR analysis, expression array analysis, and transcriptome sequencing. In spite of the known preference for certain pathogenetic pathways, we found considerable genetic heterogeneity in high‐grade (HG) as well as in low‐grade (LG) ESS. Not all HG tumors showed a YWHAE‐NUTM chimeric transcript and as many as six LGESS showed no hitherto known ESS‐related fusions. Among the transcripts identified by transcriptome sequencing and verified by Sanger sequencing, new variants of ZC3H7‐BCOR and its reciprocal BCOR‐ZC3H7 were identified as was involvement of the CREBBP and MLLT4 genes (both well known leukemia‐related genes) in two new fusions. FISH analysis identified a known EPC1‐PHF1 fusion which led to the identification of a new variant at the molecular level. The fact that around 70 genes were found differentially expressed, by microarray analysis, when comparing LGESS showing ESS‐related fusions with LGESS without such transcripts, underscores the biochemical importance of the observed genetic heterogeneity and hints that new subgroups/entities in LGESS still remain undiscovered. © 2016 The Authors. Genes, Chromosomes & Cancer Published by Wiley Periodicals, Inc.